Tolerance to multiple metal stressors in emerging non-typhoidal MDR Salmonella serotypes: a relevant role for copper in anaerobic conditions - Mourão, Joana (2017)
Objectives: Factors driving the expansion of particular MDR Salmonella serotypes/clones are not completely understood. We assessed if emergent MDR Salmonella serotypes/clones were more enriched in metal tolerance genes (e.g. to Cu/Ag) than other less frequent ones, as an additional feature to survive in environments contaminated with metals. Methods: Metal (Cu pco/Ag,Cu sil/Hg mer/As ars/Te ter) tolerance genes screening (PCR/sequencing), MICs of CuSO4/AgNO3 (aerobiosis/anaerobiosis), genetic element characterization (S1/I-CeuI PFGE) and conjugation assays were performed in a well-characterized Salmonella collection (n = 275 isolates; 2000–14; 49 serotypes/clones). Results The sil ± pco genes were detected in 37% of isolates from diverse serotypes, mainly in emergent Rissen/ST469 and Typhimurium/ST34 European clone (100%), which are mostly associated with pig settings where Cu is highly used. These genes were frequently co-located with merA ± terF and/or antibiotic resistance genes in plasmids (100–270 kb; IncHI2/IncHI1/IncN/IncFIIA; mostly transferable by conjugation) or in the chromosome. Most sil ± pco+ isolates (77%) were MDR contrasting with sil ± pco− ones (48%). The sil ± pco+ isolates presented significantly higher MICCuSO4 under anaerobiosis (MIC50/MIC90 = 28/32 mM) and MICAgNO3 after previous Ag contact (MIC50/MIC90 > 3 mM) than sil− ones (MIC50/MIC90 = 2/8 mM to CuSO4; MIC50/MIC90 = 0.125/0.16 mM to AgNO3). Use of these modified methodological approaches allowed the establishment of CuSO4/AgNO3 tolerance cut-offs to differentiate sil+ and sil− isolates, here firstly proposed. Conclusions: This study demonstrates that acquisition of Cu/Ag tolerance genes (sil/pco genes) might contribute to the emergence of particular clinically relevant MDR Salmonella serotypes/clones by facilitating their survival in diverse metal-contaminated settings, particularly in pig production. Assessment of control measures for the use and/or accumulation of metals in diverse environments are needed to prevent a wider expansion of such strains or the emergence of new ones.